Strength development of fine grained mortar containing palm oil fuel ash as a partial cement replacement - Wan Yusof, Wan Yuslinda (2014)
This study was focusing on the utilization of Palm Oil Fuel Ash (POFA) and the effect of fine sand to develop the strength of the mortar. The flexural and compressive strength of fine grained mortar (FGM) with the addition of POFA and the sand usage with a size less than 1 mm were investigated. Then, the optimum percentage of POFA as a replacement material for cement was determined. Cement was partially replaced with POFA at various percentage of 0 % to 40 % by weight of cementitious materials with three (3) samples for each percentage. The laboratory test was conducted for this study are divided into two which are properties of samples (X-ray fluorescence and particle size analyzer), and hardened mortar (compressive and flexural strength). The prism specimens size are 40 mm x 40 mm x 160 mm and were tested at the age of 7 and 28 days according to BS EN 196-1:2005: Method of Testing Cement. The results showed that the highest flexural and compression strength is at 10 % due to a factor which is the effect of POFA and fine sand produce a strong bond between the particles with the longer curing time, that is after 14 days. This is indicated that an additional of 10 % POFA in FGM is the optimal percentage of POFA as a replacement for cement